Analisis Keterampilan Guru Dalam Menutup Pembelajaran Guna Mencapai Tujuan Pembelajaran dan Membentuk Karakter Siswa di SD Inpres Kema III - Romi Mesra; Theodorus Pangalila; Abzan Laebe; Risal Risal; Nining Rahmawati (Civic Education: Media Kajian Pancasila dan Kewarganegaraan, 2023)
This study basically focuses on closure ability as an important component of teaching ability. The teacher's task in ending learning is to assess whether the goals have been achieved, whether the information has been understood by students, and to end learning activities. The ability to close class is a task completed by the instructor to conclude a lesson. In addition, the teacher's role in closing the lesson is to complete the main activity. The purpose of this study was to analyze the teacher's skills in closing lessons in order to achieve learning objectives and shape the character of students at SD Inpres Kema III. Qualitative research methods were applied in this study which was conducted to understand a phenomenon experienced by research subjects such as behavior, perceptions, motivations, actions, and so on, which are described in descriptions. The results of this study indicate that the teacher has carried out closing activities well by giving homework or assignments in closing learning activities, the teacher draws conclusions in closing learning activities, and the teacher evaluates students in closing learning activities